Designing a smart information system: the influence of feedback on energy conservation persuasion. Issue 4 (20th April 2020) - Ji, Xiang; Swoboda, Markus; Rau, Pei-Luen Patrick; Sun, Na
ABSTRACT: This study explored whether a smart information system can motivate users to conserve energy in the home environment. Three kinds of feedback information based on user decisions were discussed: emotion feedback with a happy mood, average feedback of a comparison group and ranking feedback within a comparison group. An experiment validated that all the feedbacks had a positive influence on users' energy conservation performance. Users' positive attitude toward the social group that they lived in and compared with would increased users' environmentally friendly behaviours. Finally, several suggestions on the design of energy feedback are provided.